Nutritional correlates of monetary diet cost in young, middle-aged and older Japanese women - Keiko Shiraki; Kentaro Murakami; Hitomi Okubo; M. Barbara E. Livingstone; Satomi Kobayashi; Hitomi Suga; Satoshi Sasaki (Journal of Nutritional Science, 2017)
Studies in many Western countries have consistently shown that monetary diet cost is positively associated with diet quality, but this may not necessarily be the case in Japan. This cross-sectional study examined the nutritional correlates of monetary diet cost among 3963 young (all 18 years old), 3800 middle-aged (mean age 48 years) and 2211 older (mean age 74 years) Japanese women. Dietary intakes were assessed using a comprehensive self-administered diet history questionnaire for young and middle-aged women and a brief self-administered diet history questionnaire for older women. Monetary diet cost was estimated using retail food prices. Total vegetables, fish and shellfish, green and black tea, white rice, meat, fruit and alcoholic beverages contributed most (79–89 %) to inter-individual variation in monetary diet cost. Multiple regression analyses showed that monetary diet cost was negatively associated with carbohydrate intake, but positively with intakes of all other nutrients examined (including not only dietary fibre and key vitamins and minerals but also saturated fat and Na) in all generations. For food group intakes, irrespective of age, monetary diet cost was associated inversely with white rice and bread but positively with pulses, potatoes, fruit, total vegetables, fruit and vegetable juice, green and black tea, fish and shellfish, and meat. In conclusion, in all three generations of Japanese women and contrary to Western populations, monetary diet cost was positively associated with not only healthy dietary components (including fruits, vegetables, fish and shellfish, dietary fibre, and key vitamins and minerals), but also less healthy components (including saturated fat and Na).